2003
DOI: 10.1034/j.1600-0714.2003.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastomatous calcifying odontogenic cyst: a rare histologic variant

Abstract: Calcifying odontogenic cyst (COC) is an uncommon developmental odontogenic cyst first described by Gorlin in 1962. It is considered as extremely rare and accounts for only 1% of jaw cysts reported. Because of its diverse histopathology, there has always been confusion about its nature as a cyst, neoplasm or hamartoma. Several subclassifications have been proposed. Here, we present a case of calcifying odontogenic cyst with ameloblastic proliferation - an extremely rare histologic variant. The classical histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 7 publications
0
17
1
Order By: Relevance
“…It presents with a painless slowly growing lesion affecting young adults in the second decade of life without gender predilection (4). Kamboj, Aithal, and Ide et al reported cases of ameloblastomatous COC with swelling of mandible, which is inconsistent with our study (1,3,10). In the present study, ameloblastomatous COC occurred in a man in fourth decade of life.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…It presents with a painless slowly growing lesion affecting young adults in the second decade of life without gender predilection (4). Kamboj, Aithal, and Ide et al reported cases of ameloblastomatous COC with swelling of mandible, which is inconsistent with our study (1,3,10). In the present study, ameloblastomatous COC occurred in a man in fourth decade of life.…”
Section: Discussioncontrasting
confidence: 57%
“…In the present study, ameloblastomatous COC occurred in a man in fourth decade of life. Aithal and Singh presented female cases in the third decade of life and Menal reported a case of in a man in the third decade (3,8). COC is generally a unilocular radiolucent lesion; some of them are well-defined and others may be ill-defined or poorly defined in radiology (1, 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the new WHO classification of histological typing of odontogenic tumors, the COC constitutes a benign cystic neoplasia that presents an epithelium similar to an ameloblastoma, with ghost cells that may display calcifications (9). COC is an uncommon lesion accounting for 1% of jaw cysts (9,10); the ameloblastomatous COC is even less common. Of 43,500 cases diagnosed by the Oral Pathology diagnostic service at the Indiana University School of Dentistry, only 34 cases of COC were reported.…”
Section: Discussionmentioning
confidence: 99%